(untitled) (JED (Jurnal Etika Demokrasi), 2025)
This study investigates the level of public voter participation in the 2024 single candidate regional election in Banyumas Regency, addressing the urgent issue of declining electoral engagement and the substantive quality of democracy under the Pancasila framework. The primary objective is to analyze the institutional, procedural, and sociocultural factors contributing to the emergence of a single candidate and to assess their effects on voter behavior and democratic legitimacy. Employing a quantitative cross-sectional survey design with stratified sampling, this research targets registered voters and utilizes descriptive and inferential statistical analysis to interpret participation patterns. The findings reveal that coalition disintegration, administrative barriers in candidate nomination, and pragmatic political alliances significantly limited electoral competition and reduced meaningful public choice, resulting in decreased voter turnout and a notable rise in protest voting through the empty ballot option. The study concludes that single candidate elections undermine participatory democracy, necessitating institutional reforms and innovative civic education to revitalize democratic engagement. The novelty of this research lies in its integrated analysis of protest voting and cognitive mobilization in an Indonesian local election context, offering fresh insights into the interplay between institutional structures and citizen agency. By elucidating these dynamics, the study contributes substantially to the advancement of knowledge on electoral participation, democratic resilience, and the improvement of local electoral governance.